2021
DOI: 10.3892/etm.2021.10467
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise influences the microRNA profiles in the bone tissues of mice

Abstract: As an important regulator involved in cell activity, microRNAs (miRNAs) are important in the process of exercise influencing bone metabolism. The present study aimed to detect and select differentially expressed miRNAs in the bone tissues of mice trained on a treadmill, predict the target genes of these differentially expressed miRNAs and lay a foundation for exploring the effect of treadmill training on bone metabolism through miRNAs. In this experiment, after the mice were trained on a treadmill for 8 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…BSP was suggested to be the early marker for osteogenic differentiation of stem cells [44]. The OCN gene encodes protein secreted by osteoblasts that regulates bone remodeling [45]. COL1A1 is also known as an osteogenic marker, and the impairment in collagen formation due to mutation of COL1A1 may lead to fragility of bone [46].…”
Section: Discussionmentioning
confidence: 99%
“…BSP was suggested to be the early marker for osteogenic differentiation of stem cells [44]. The OCN gene encodes protein secreted by osteoblasts that regulates bone remodeling [45]. COL1A1 is also known as an osteogenic marker, and the impairment in collagen formation due to mutation of COL1A1 may lead to fragility of bone [46].…”
Section: Discussionmentioning
confidence: 99%
“…The potential upstream mediators of osteogenesis and neurogenesis in mice femora were assessed. Previous literature explored the effects of 8-week treadmill exercise training (13 m/min; 9° slope; for 40 min/day; 6 days/week) on the miRNA expression in the femora of 4-month-old male BALB/c mice ( Yang et al, 2021 ). Re-examination of the microarray dataset (GSE179201) shown in Figure 4A revealed that a total of 191 out of 1,900 miRNAs were differentially expressed ( p < 0.05) between the non-exercise and aerobic exercise training groups.…”
Section: Resultsmentioning
confidence: 99%
“…There was an increase in the expression of alkaline phosphatase and osteocalcin in the femur of rats given treadmill intervention, where these two indicators have association with the formation and mineralization of bone matrix. Treadmill exercise can increase the maturation and differentiation of bone tissue (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%